MicroRNA miR-24-3p Reduces Apoptosis and Regulates Keap1-Nrf2 Pathway in Mouse Cardiomyocytes Responding to Ischemia/Reperfusion Injury. (2nd December 2018) - Xiao, Xu; Lu, Zhigang; Lin, Victor; May, Adam; Shaw, Daniel H.; Wang, Zhihao; Che, Briana; Tran, Kyle; Du, Hongjun; Shaw, Peter X.
Abstract : In recent years, microRNAs (miRNAs) have received increasing attention for their role in ischemia/reperfusion injury (I/RI), and many miRNAs have been demonstrated to play a very important role in cardiac I/RI. The miRNA miR-24-3p is a tumor suppressor that regulates multiple tumors; however, it remains unclear whether the expression level of miR-24-3p is altered in cardiac cells under I/RI. In this study, we used mouse primary cardiomyocytes and the H9C2 cardiomyocyte cell line to perform in vitro stimulated ischemia/reperfusion (SI/R) and then detected miR-24-3p expression level using quantitative real-time PCR (qRT-PCR). We discovered that the expression of miR-24-3p was significantly increased in cardiomyocytes following SI/R, and that the miR-24-3p level was inversely correlated to the ischemia marker HIF-1a. Furthermore, we transfected cardiomyocytes with miR-24-3p mimic or inhibitor to explore the role of miR-24-3p in cardiomyocyte ischemia/reperfusion injury in vitro . We performed flow cytometry to detect the apoptotic rate of H9C2 cardiomyocytes and found that the transfection of miR-24-3p mimic resulted in the decrease of the apoptosis rate of cardiomyocytes after SI/R, whereas the transfection of miR-24-3p inhibitor increased the number of apoptotic cardiomyocytes. These data suggest that the overexpression of miR-24-3p could reduce in vitro myocardial cell apoptosis induced by I/R injury. Finally, we applied the dual luciferase reporter gene system to verify whether miR-24-3p targets the Keap1 gene, and found that the luciferase signal intensity from a vector carrying the Keap1 wild-type reporter gene was significantly reduced after transfection with miR-24-3p mimic. The Keap1 protein level was also reduced following the transfection of miR-24-3p. The results from this study suggest a novel function of miR-24-3p in protecting cardiomyocytes from ischemia/reperfusion injury by the activation of the Nrf2-Keap1 pathway.